FOTOELEMENT VOLT-AMPER XARAKTERISTIKALARIGA ELEKTROMAGNIT TO‘LQINNING TA’SIRI - G‘ulomov, G‘.; Majidova, G.N.; Muxitdinova, F.R.; Mamarizayeva, S.O. (SCIENCE and SOCIETY, 2022)
Usually, both heating and rectification are associated with an increase in recombination currents, so their currents and EMF have the same direction. From this we can say that the microwave field always generates currents in the correct direction in the p-n junction diode.
Keywords: quasi-Fermi level; photoelectron motive forse; microwave; recombination; generation